Sungai Udang Port : bits development and challenges ... [et al.] / [mikrofilem] - 330241 Bahtiar Affendy Hashim (Skudai : Universiti Teknologi Malaysia, 1998)
Project Paper (Bachelor of Management Technology (Maritime Transportation)) - Universiti Teknologi Malaysia, 1998